Peran Guru dalam Mengoptimalkan Sumber Belajar di MA Al-Mahrusiyah Lirboyo Kota Kediri - Nurul Atikoh; Syafik Ubaidila (Universitas Islam Tribakti Lirboyo Kediri, 2023)
Learning resources have an important role in determining the learning process so that learning becomes effective and efficient in achieving goals. This research uses a type of field research with a descriptive-qualitative approach. The results of optimizing learning resources: (1) In terms of conditions, the addition of laboratory space, the projector originally numbered 6 to 17. There are 8 internet sources that can be accessed. Addition of laboratory inventory 116 practical tools & 44 experimental materials in the science laboratory, 13 inventory for the social studies laboratory, 41 laptops in the Language / Multimedia laboratory, 14 inventory in the religion laboratory and one glass cabinet. (2) How teachers optimize learning resources by using existing tools and materials, such as chemicals, corpse menekin, projectors, and textbooks. (3) There is an increase in laboratory usage & projector loans. Reading interest has increased due to the addition of reference materials other than LKS books, several novels and 2 computers that can be used to access books or other assignment needs.